Urgensi Evaluasi Materi Ajar Bahasa Arab - Malik Husin (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2026)
This study aims to analyze the urgency of evaluating Arabic language teaching materials at the secondary level by comprehensively examining linguistic, pedagogical, and cultural aspects. The research employed a qualitative approach with an evaluative design. Data were collected through document analysis of 12 textbook chapters, interviews with three Arabic language teachers, and classroom observations involving 64 students. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the teaching materials are predominantly grammar-oriented (40%), while communicative skills such as speaking (7%) and listening (5%) receive limited emphasis. Approximately 62% of students reported difficulty understanding texts independently, and 75% of assessments were grammar-based. In terms of cultural content, 80% focused on Middle Eastern contexts with limited integration of local cultural elements. These findings indicate an imbalance between structural competence and communicative function, as well as insufficient intercultural orientation. The study concludes that systematic evaluation of Arabic teaching materials is essential to ensure alignment among linguistic, pedagogical, and cultural competencies. The novelty of this research lies in proposing an integrative evaluation framework based on three dimensions (linguistic–pedagogical–intercultural), offering a comprehensive model for developing more communicative and contextually relevant Arabic teaching materials